The Coaxium® Wheat Production System: A New Herbicide-Resistant System for Annual Grass Weed Control and Integrated Weed Management. (1st August 2021) - Bough, Raven; Westra, Phillip; Gaines, Todd; Westra, Eric; Haley, Scott; Erker, Brad; Shelton, Chad; Reinheimer, Jason; Dayan, Franck
The authors discuss the importance of wheat as a global food source and describe a novel multi-institutional, public-private partnership between Colorado State University, the Colorado Wheat Research Foundation, and private chemical and seed companies that resulted in the development of a new herbicide-resistant wheat production system.